Transgenic Mouse Models of Parkinson's Disease and Huntington's Disease - D. Skaper, Stephen; Giusti, Pietro (CNS & Neurological Disorders - Drug Targets, 2010)
Parkinson's disease (PD) is a chronic progressive neurodegenerative movement disorder characterized by a profound and selective loss of nigrostriatal dopaminergic neurons. Another neurodegenerative disorder, Huntington's disease (HD), is characterized by striking movement abnormalities and the loss of medium-sized spiny neurons in the striatum. Current medications only provide symptomatic relief and fail to halt the death of neurons in these disorders. A major hurdle in the development of neuroprotective therapies is due to limited understanding of disease processes leading to the death of neurons. The etiology of dopaminergic neuronal demise in PD is elusive, but a combination of genetic and environmental factors seems to play a critical role. The majority of PD cases are sporadic; however, the discovery of genes linked to rare familial forms of disease and studies from experimental animal models has provided crucial insights into molecular mechanisms of disease pathogenesis. HD, on the other hand, is one of the few neurodegenerative diseases with a known genetic cause, namely an expanded CAG repeat mutation, extending a polyglutamine tract in the huntingtin protein. One of the most important advances in HD research has been the generation of various mouse models that enable the exploration of early pathological, molecular, and cellular abnormalities produced by the mutation. In addition, these models for both HD and PD have made possible the testing of different pharmacological approaches to delay the onset or slow the progression of disease. This article will provide an overview of the genetics underlying PD and HD, the animal models developed, and their potential utility to the study of disease pathophysiology.
Keywords: polyglutamine disease